Proteomics to assess myocardial remodelling in human heart failure and explore the effect of medications and comorbidities. (10th June 2022) - Barallobre-Barreiro, J; Radovits, T; Fava, M; Daroczi, L; Hasman, M; Schmidt, L; Baig, F; Theofilatos, K; Crespo-Leiro, MG; Domenech, N; Merkely, B; Mayr, M
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): British Heart Foundation Background: Myocardial remodelling is a hallmark of heart failure (HF). Our previous proteomics analyses demonstrated a profound effect of beta blockers on cardiac extracellular matrix composition in ischaemic HF patients (1). No comprehensive proteomics characterizations has been performed in non-ischaemic HF patients. Methods: Mass spectrometry was used to analyze intracellular and extracellular protein extracts from left ventricular samples obtained from patients with ischemic (n=65) and non-ischaemic (n=114) HF after heart transplantation, as well as non-failing controls (n=19). All HF patients had ventricular dilatation and reduced ejection fraction (EF%). Results: The proteomics comparison across 198 cardiac samples with two tissue extracts revealed hallmarks of HF in both groups of patients compared to controls, including elevated levels of atrial natriuretric peptides and the fibroblast marker vimentin, as well as decreases in creatine kinase M/B, troponin C, and myosin light chain 2 (Figure 1). In comparison to ischaemic HF patients, non-ischaemic HF patients showed elevated levels of proteins involved in proteasome activation, consistent with the notion of increased protein degradation in cardiomyocytes even at the end stage of the disease (2). Despite similar clinical characteristics, myocardial remodelling in response to HF medications and the presence of comorbidities was different between the two HF groups. In ischaemic HF patients the use of β-blockers resulted in reduced proteoglycan deposition. In non-ischaemic patients, few protein changes were associated with medication. Instead, comorbidities such as atrial fibrillation and hypertension were critical determinants of myocardial protein remodelling in these HF patients (Figure 2). Notably, hypertensive HF patients showed a marked reduction in angiotensin converting enzyme 2 (ACE2) compared to normotensive patients, and this was accompanied by a reduction in Cysteine And Glycine Rich Protein 3 (CSRP3), a key player in the organization of cytosolic structures in cardiomyocytes, and the nuclear lamina proteins lamin A/C and B. The inflammation-related galectin 3-binding protein was reduced in hypertensive patients as were the extracellular proteases matrix metalloprotease 2, cathepsin G and chymase 1. Conclusion: Our study constitutes the largest proteomics analysis of HF to date. We observed distinct protein remodelling processes in ischaemic and non-ischaemic HF patients and discerned the myocardial effects of medications and comorbidities such as hypertension.